ANALISIS SISTEM PERFORMANSI TRANSMITTER FM BERBASIS RASPBERY - Fajar Ramadhan; Sigit Kusmaryanto; Akhmad Zainuri (Jurnal Mahasiswa TEUB, 2023)
Raspberry Pi (Raspi) is a single-board computer (single-board circuit; SBC) that can be used to run office programs, computer games, and as a media player to high-resolution video. The Raspberry Pi has advantages that resemble computers in general, in every way. on the computer functions can also be done with the Raspberry Pi. This paper discusses the application of the raspberry Pi 3b+ as a VHF receiver at a frequency of 136 MHz-174 MHz using RTLSDR R2832U. The author uses Handy-Talkie as a transmitter for FM waves at a VHF frequency (136 MHz-174 MHz). Raspberry Pi 3 implementation with RTL-SDR R2832U to receive FM waves using GNU Radio and GQRX software. The operating system used in this research is Raspberry Pi OS. The results show that the Raspberry Pi device can be used to receive FM waves at the VHF frequency (136 MHz-174 MHz) with SNR 48.7 dB at 136.025 MHz Dipole antenna examined using VNA (Vector Network Analyzer) with length 52.4 cm on each side and linear shape that can receive signal with VSWR 1.48:1 on frequency 136-174 MHz and gain -14.2 dBm on frequency 136 MHz Keywords: Raspberry Pi, RTL-SDR, FM Signal, Software Defined Radio